Accidental Dural Puncture Management: 10-Year Experience at an Academic Tertiary Care Center. Issue 1 (March 2017) - Bolden, Norman; Gebre, Ermias
Abstract : ( Reg Anesth Pain Med. 2016;41:169–174) Epidural analgesia is the most effective form of analgesia for labor pain. However, the placement of an epidural catheter is associated with complications, such as accidental dural puncture (ADP) and postdural puncture headache (PDPH). The management of an ADP may be either resiting of the epidural catheter at another interspace or catheter insertion into the intrathecal space and use of the spinal catheter for labor analgesia. This study aimed to assess the impact of the use of spinal catheters and the administration of intrathecal saline on PDPH incidence and subsequent epidural blood patch (EBP) requirement at a tertiary care facility.